Penguatan Fungsi Dan Prinsip Manajemen Pendidikan Dalam Mendukung Transformasi Digital - Ida Hapni Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the improvement functions and principles of education management in supporting digital transformation, emphasizing the use of technologies such as school management systems (SIS), learning management systems (LMS), and performance monitoring applications. The research method used was a literature review of 15 scientific articles published between 2020 and 2024, which discussed relevant issues related to digital education management. The results of the study indicate that the main functions of management in education, namely planning, organizing, directing, and controlling, are increasingly important when integrated with the principles of effectiveness, efficiency, innovation, and participation. The planning function emphasizes the development of school digitalization strategies, organizing plays a role in allocating human and technological resources, directing includes empowering teachers and students in the use of technology, while controlling functions to ensure the quality of education services is maintained during the digital transformation process. In addition, adaptive education management principles are essential. Effectiveness emphasizes the measurable achievement of digitalization goals, efficiency highlights the optimal use of resources, innovation encourages the creation of creative technology-based learning strategies, and participation invites all education stakeholders to be actively involved. Key factors supporting successful digital transformation include infrastructure readiness, improved teacher digital competency, visionary and adaptive leadership, and government policy and political support. However, this study also identified several challenges, such as disparities in access to digital infrastructure between regions, limited digital literacy among teachers and education personnel, and resistance to change. Therefore, improving the functions and principles of educational management in line with technological developments is believed to strengthen the quality, equity of access, and competitiveness of education in the digital era.